Pemulihan Perempuan Penyintas Kekerasan Berbasis Gender Siber (KBGS): Studi Kasus Dua Perempuan Penyintas KBGS dalam Mempertahankan Penghidupannya - Rosydinda Deselia; Elizabeth Kristi Poerwandari (Journal of Health Science and Prevention, 2023)
This article aims to explore the recovery process of two women survivors of online gender-based violence and their efforts to maintain their livelihoods. This article shows the bondage of violence with the spaces in survivors lives and the livelihood strategies they employ. The method used is a qualitative feminist perspective with data collection techniques carried out by in-depth interviews via online. The data were then analyzed using the Sphere, Time, and Violence (STV) framework by Elias and Rai, which explains deeper about the inequality women experienced in their lives based on 3 aspects; space, time, and violence. The results of the study show two main findings: first, online gender-based violence experienced by women is intertwined with women's roles and living spaces. Women got economic and psychological impacts along with victim blaming and negative stigma from the environment. Second, women survivors seek different coping strategies to survive and recover. Both of the subjects limit their access to communication, carry out technical efforts, and report the case they experienced to the authorities. Unfortunately, the state does not guarantee the recovery of online gender-based violence victims, so there are losses and costs that must be borne by the survivors themselves